Geographic variation in body size and its relationship with environmental gradients in the Oriental Garden Lizard, Calotes versicolor. Issue 9 (2nd April 2018) - Wei, Xiaomei; Yan, Linmiao; Zhao, Chengjian; Zhang, Yueyun; Xu, Yongli; Cai, Bo; Jiang, Ni; Huang, Yong
Abstract: Patterns of geographic variation in body size are predicted to evolve as adaptations to local environmental gradients. However, many of these clinal patterns in body size, such as Bergmann's rule, are controversial and require further investigation into ectotherms such as reptiles on a regional scale. To examine the environmental variables (temperature, precipitation, topography and primary productivity) that shaped patterns of geographic variation in body size in the reptile Calotes versicolor, we sampled 180 adult specimens (91 males and 89 females) at 40 locations across the species range in China. The MANOVA results suggest significant sexual size dimorphism in C. versicolor ( F 23, 124 = 11.32, p < .001). Our results showed that C. versicolor failed to fit the Bergmann's rule. We found that the most important predictors of variation in body size of C. versicolor differed for males and females, but mechanisms related to heat balance and water availability hypotheses were involved in both sexes. Temperature seasonality, precipitation of the driest month, precipitation seasonality, and precipitation of the driest quarter were the most important predictors of variation in body size in males, whereas mean precipitation of the warmest quarter, mean temperature of the wettest quarter, precipitation seasonality, and precipitation of the wettest month were most important for body size variation in females. The discrepancy between patterns of association between the sexes suggested that different selection pressures may be acting in males and females. Abstract : The analysis of geographic variation in Calotes versicolor body size showed significant sexual dimorphism, converse Bergmann's rule. The relationship between geographic variation in body size and environmental factors suggested that the most important predictors of variation in body size of C. versicolor differed for males and females, but mechanisms related to heat balance and water availability hypotheses were involved in both sexes. These divergences suggested that different selection pressures may be acting on them.